To bat or not to bat? - Batting eye of elite batters: a preliminary report - Chen, Y.; Lu, Y.; Lee, P.; Yen, N. (Proceedings of the 2nd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2014)
In this study, we investigated the difference of the batting decision in advanced (n=18) and intermediate baseball batters (n=12) by asking them to make a swing judgement and then to recognize the pitch after they viewed it, given a draw situation of full count (2 strikes and 3 balls), 2 out, and full base at the last inning in a match. We also manipulated the length of the video sequence of the pitch that was presented to the batters to investigate the group difference when batters could see only fraction of pitch motion and the baseball trajectory. Advanced players showed higher batting rate than the intermediate players, particularly when they could see very limited sequence of the strikes pitches. This result reflected their more accurate and quicker response for strikes as compared to intermediate players. Interestingly, a similar tendency was also found for ball pitches. This result could be explained by that advanced players considered those balls as potential strikes subjecti vely; or that they were intended to make a foul ball, for getting a further pitch count as a positive strategy. Intermediate players instead, in this situation were not sure whether to bat or not, resulting a higher percentage of uncertain decision. We concluded that to make a batting decision correctly and strategically could be important elements in achieving high level batting.